Innovative strategies for co-delivering antigens and CpG oligonucleotides - Krishnamachari, Yogita (2009)
Cytosine-phosphorothioate-guanine oligodeoxynucleotides (CpG ODN) is a recent class of immunostimulatory adjuvants that includes unmethylated CpG dinucleotide sequences similar to those commonly found in bacterial DNA. CpG ODN specifically triggers toll like receptor 9 (TLR9), which is found within phagoendosomes of antigen presenting cells (APCs) such as dendritic cells (DCs). CpG ODN triggers activation and maturation of DCs and helps to increase expression of antigens. CpG ODN can be used to induce polarized Th1 type immune responses. Several studies have shown that antigens and CpG ODN must be co-localized in the same APC to generate the most potent therapeutic antigen-specific immune responses. Delivery vehicles can be utilized to ensure co-delivery of antigens and CpG ODN to the same APCs and to significantly increase uptake by APCs. These strategies can result in antigen-specific immune responses that are 5 to 500-fold greater than administration of antigen alone. In this review, we discuss several recent and innovative strategies to co-delivering antigens and CpG ODN adjuvants to APCs. These approaches include the utilization of conjugate molecules, multi-component nanorods, liposomes, biodegradable microparticles, pulsatile release chips and cell-microparticle hybrids.